## Number Puzzle #182

Check your answer:-

**Answer**: 4

**Explanation**: Diagonal numbers are multiplication of the bottom number and 3

8*3 = 24

5*3 = 15

x*3 = 12 =? x = 4

Number puzzles have specific set of rules, you first has to figure out the pattern being followed and then answer the puzzle according to the pattern.

Number puzzles are a part of many competitive examinations, these also helps you improve your logical thinking and above all these are fun to crack !!!

If

2×3=15

2×5=20

2×7=30

2×11=?

**What will be the value Burger + FrenchFries x ColdDrink ?**

Check your answer:-

If you see there are 3 variables and 3 equations, we can solve the equations and get the variables values and than we can find the value of fourth equation.

From the first equation we can say that ColdDrink = 10

than from the second Burger = (20 – 10)/2 = 5

and from the third equation FrenchFries= (9 – 5)/4 = 1

Thus Burger + FrenchFries * ColdDrink = 5 + 1*10 = 15

here as per BODMAS 5 + 1*10 will be 5 + 10 = 15

What will be the next number in this series?

1 , 17 , 98 , 354 , ?

-1¹²¹ -1¹²² -1¹²³ -1¹²^⁴ =?

Check your answer:-

Click here to See Solution
-1^n is 1 (if n is even) OR -1 (in n is odd)

but in this equation power is on 1 not -1

-1¹²¹-1¹²² -1¹²³-1¹²^⁴ = -1-1-1-1 = -4

What will be the next number in this series?

11,15,19,18,26,21,32, 24,37,____

If 1*36=36

8*23=23

8*67=1

Then

9*10=?

0, 1, 5, 19, 65, 211, ?

Check your answer:-

Answer: 665

explanation:

it follows this equation** 3^n – 2^n** where n is integer starting from 0

explanation:

it follows this equation

thus

3^0 – 2^0 = 1 – 1 = 0

3^1 – 2^1 = 3 – 2 = 1

3^2 – 2^2 = 9 – 4 = 5

3^3 – 2^3 = 27 – 8 = 19

3^4 – 2^4 = 65

3^5 – 2^5 = 211

3^6 – 2^6 = 729 – 64 = 665

There is one more way to solve this

**3*previous number + 2^(n-1)**

0x3+1=1;

1×3+2=5;

5×3+4=19;

19×3+8=65;

65×3+16=211;

211×3+32=665;

**wondering how it is possible?**

lets solve 3*previous number + 2^(n-1)

=> 3*(3^(n-1) – 2^(n-1)) + 2^(n-1)

=> 3^n – (2+1)*2^(n-1) + 2^(n-1)

=> 3^n – 2^n – 2^(n-1) + 2^(n-1)

=> 3^n – 2^n i.e. our first equation

- 1
- 2
- 3
- …
- 21
- Next Page »